SOSIALISASI PROGRAM KETAHANAN PANGAN MELALUI PEMANFAATAN LAHAN DI SDN ARJASA 1 KECAMATAN ARJASA KABUPATEN JEMBER - Arini, Silvia Fitri Mei; Pratama, Yudha (PAPUMA: Journal of Community Services, 2024)
There is still school yard land which has not yet been maximized. So solutions and innovation are needed in using it. This aims to maximize less productive school yard land so that it can support food security. The aim of this activity is to maximize the potential of unused school land into productive land through cultivating plants to support the national food security program. The methods used are the lecture method and direct practice method. The results obtained from the activity are a source of information for all school residents at SDN Arjasa 1 regarding cultivation techniques and innovations regarding the use of school yard land to support food security programs.